Model Berbasis Agen untuk Pengenalan Produk Baru dengan Twitter - Bintoro, Bambang Purwoko Kusumo (Business and Management Review, 2012)
In less than 4 years since its introductions, Twitter has become the fastest growing social networking tool. Working very much the same as a blog, it has been used widely by businesses as well as individuals to share information, introduce new product/idea, etc.  Using Twitter,  a person  has the choice whether or not to  forward  (re-tweet)  the message from/to his/her friends or social networks that he/she belongs to. The result of online survey revealed some factors (taste, price, availability, packaging and image), which affect the decision to re-tweet or not an information pertaining new food product following the Diffusion of Innovations model.  On the other hand, the independent and autonomous behavior of members in a social network such as Twitter satisfies the characteristics of Agent Based Simulation model. Using NetLogo software, this paper aims to  disclose  the result  of  an  Agent Based Simulation model which showed when and why a person will or will not re-tweet a message that he/she received from his/her friends or social networks that he / she belongs to by applying the concept of Diffusion of Innovations Keywords: twitter, social networking, agent based simulation, diffusion of innovation, NetLogo